Modelo de política óptima de dividendos (Model for a dividend optimal policy) - Nuñez Pérez, Jorge; Rositas Martínez, Juan; Medina Elizondo, Manuel (Facultad de Contaduría Pública y Administración U.A.N.L., 2013)
Abstract. This research addresses one of the fundamental decisions of corporate finance: the dividend policy. It is formulated a model whose building blocks are the theory of irrelevance of the dividends of Modigliani and Miller (as a general context), the signaling model of John Lintner, and the model of Michael S. Rozzef of minimization of agency cost and transaction costs. The construction of the theoretical model of optimal dividend policy proposed here highlights the advantages of the axiomatic definition of the theory of Modigliani and Miller, by its logical contribution, and intends to propose a new formulation with respect to the determination of level of payment of dividends in the corporations. Therefore we relax the assumptions specified by Modigliani and Miller related to liquidity indifference, absence of uncertainty, agency costs and transaction cost, also we explore the possibility of presence of asymmetric information. In such circumstances, for the model exposed here and by means of a binary logistic regression analysis is tested the influence of profits, the information content of dividends, the clientele effect and agency costs to define policy dividends of the corporations in Mexico.